Clinical Characteristics of Posner-Schlossman Syndrome Patients in China. (20th January 2023) - Gao, Tingting; Song, Sijia; Ke, Xianghan; Li, Shushan; Zhang, Di; Chen, Xuhao; Zhang, Chun
Abstract : Background . To explore the clinical characteristics of Posner-Schlossman syndrome (PSS) patients in China, especially the risk factors associated with the dynamic changes of corneal endothelial cell (CEC) density and retinal nerve fiber layer (RNFL) thickness during the course of the disease. Methods . In this retrospective cohort study, patients consequently suffering from PSS were recruited. Patients data including gender, age of onset, frequency of attack, and disease duration. We performed detailed ophthalmology examinations including intraocular pressure (IOP), best-corrected visual acuity (BCVA), slit-lamp examination, optical coherence tomography (OCT), assessing RNFL thickness, and determined CEC density in the outpatient department. The unaffected eyes served as control. Results . We recruited 121 patients (eyes, n = 125 ), including 69 (57.0%) males and 52 (43.0%) females with Posner-Schlossman syndrome. The age of first-onset was 33.81 ± 13.63 years old. The majority of these patients were aged 20-50 years (80.2%). The peak IOP was 47.67 ± 13.31 mmHg in the affected eyes. The frequency of PSS attack was 2.7 ± 3.7 times per year. The disease duration was 9.5 ± 10.4 years. Among all patients, there were 27 (22.31%) patients with a history of digestive disorders, 25 (20.66%) patients with a history of allergies, and 24 (19.83%) patients with a history of infectious disease. In the affected eyes, CEC density (2532.94 ± 490.83 /mm 2 vs. 2777.13 ± 356.87 /mm 2, p < 0.001 ), the RNFL thickness of four quadrants (superior 105.46 ± 29.86 μ m vs. 121.33 ± 17.30 μ m, p < 0.001 ; temporal 74.58 ± 22.21 μ m vs. 81.94 ± 18.20 μ m, p = 0.009 ; inferior 110.50 ± 33.42 μ m vs. 128.29 ± 14.39 μ m, p < 0.001 ; nasal 54.85 ± 14.48 μ m vs. 63.49 ± 15.40 μ m, p < 0.001 ) and central papillary (87.11 ± 21.18 μ m vs. 99.18 ± 7.97 μ m, p < 0.001 ) were significantly reduced compared to the fellow eyes. The disease duration and recurrent frequency were significantly associated with CEC density (p < 0.001 and p = 0.029 ) and the disease duration was significantly associated with RNFL thickness (p = 0.002 ). Conclusions . In this study, CEC loss and RNFL thinning were present in the affected eyes. Our results indicated that disease duration and recurrent frequency played an important role in the progression of PSS.